"Why Persephone?" investigating the unique position of Persephone as a dying god(dess) offering hope for the afterlife - Goodwin, Grant (Rhodes University, Faculty of Humanities, School of Languages, 2015)
Persephone's myth is unique, as it was the central narrative of one of the most prominent ancient mystery religions, and remains one of the few (certainly the most prominent) ancient Greek myths to focus on the relationship of a mother and her daughter. This unique focus must have offered her worshippers something important that they perhaps could not find elsewhere, especially as a complex and elaborate cult grew around it, transforming the divine allegory of the changing seasons or the storage of the grain beneath the earth, into a narrative offering hope for a better place in the afterlife. To understand the appeal of this myth, two aspects of her worship and mythic significance require study: the expectations of her worshippers for their own lives, to which the goddess may have been seen as a forerunner; and the mythic frameworks operating which would characterise the goddess for her worshippers. The myth, as described in The Hymn to Demeter, is initially interpreted for its literary meaning, and then set within its cultural milieu to uncover what meaning it may have had for Persephone's worshippers, particularly in terms of marriage and death, which form the initial motivating action of the myth. From this socio-anthropological study we turn to the mythic patterns and motifs the story offers, particularly the figure of the goddess of the Underworld (primarily in the influential Mesopotamian literature), and the Dying-Rising God figure (similarly derived from the Near East). These figures, when compared to the Greek goddess, may both reveal her unique appeal, and highlight the common attractions that lie in the figures generally. By this two-part investigation, on the particular culture's expectations and the general mythic framework she exists in, Persephone's meaning in her native land may be uncovered and understood.
Keywords: Mythology, Greek; Gods, Greek; Future life; Greece -- Religious life and customs; Persephone -- (Greek deity)